Improving the organizational and economic mechanisms for the development of international franchise activities in Uzbekistan - Khodjaev Anvar Rasulovich (THE INNOVATION ECONOMY, 2026)
This article examines the issues of analysis and identification of ways to improve the organizational and economic mechanisms for the development of international franchising activities in Uzbekistan. In recent years, the Republic of Uzbekistan has taken important steps to deepen economic reforms and integrate into the global econ omy. Within the framework of the Action Strategy for five priority areas of development of Uzbekistan in 2017-2021, special attention is paid to the development of entrepreneurship, attracting foreign investment and liberalization of the economy. The development of international franchising is important in this process, since the franchising model allows local entrepreneurs to introduce innovative approaches to doing business, improve the quality of service and introduce global brands to the domestic market.